I keep turning the sound into being (2014)
From a mischievous child to a painter of sounds, Santiago Yahuarcani´s testimony is moving because of its sense of humor and its unusual route. His solitary childhood experiments with some mushrooms he found on the way to his mother´s garden served him, years later, as a source of inspiration to create new figures and make a living for his own children by selling his art. Born to a Uitoto mother and a Cocama father, Santiago followed, not knowingly, the steps of Fídoma, the hero of the Aymenu clan oral history who brought color to all the being of the forest. Santiago, also brought color to its sounds.